Challenges of employing scientific research to support economic growth in Arab Countries - Sohaila Abdul Zahra Mastour Al-Hujaim; Abeer Mohammed Jassim; Sarah Abdel Reda Salman (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
Arab countries face many challenges in investing their scientific and research capabilities in order to achieve economic growth and reach the desired development goals. These challenges include the absence of clear policies that link scientific research with development plans, as well as weak funding allocated to scientific research, in addition to weak coordination between universities and research centers on the one hand and economic sectors on the other hand. Brain drain abroad has also led to a lack of competencies and expertise needed to develop and grow local economies, not to mention weak infrastructure and the absence of an environment that supports creativity and innovation, which requires the development of comprehensive strategies that enhance scientific research skills and provide the necessary incentives for scientists and researchers while strengthening the link between academic circles and economic sectors.